Metallo-beta-lactamase VIM-2 in clinical isolates of Pseudomonas aeruginosa from Portugal - Cardoso, O (2015)
Resistance to carbapenems is emerging, and it is a great problem to therapeutics. Three isolates of Pseudomonas aeruginosa from a Portuguese hospital identified in urine and sputum, in 1995, presented a high-level resistance to imipenem (32 mg/L). Afterward, one isolate of P. aeruginosa recovered from urine of an ambulatory patient in 1998 showed high resistance to imipenem. and meropenem. The resistance to carbapenems in these strains was associated with the production of a class B beta-lactamase, as was demonstrated by imipenem hydrolysis and inhibition by EDTA. Using primers described for bla(IMP) and bla(VIM) the amplification of the latter was observed in all isolates and a VIM-2 metallo-enzyme was identified. The pulsed-field gel electrophoresis (PFGE) patterns of these isolates were indistinguishable, suggesting dissemination to the community of this VIM-2 producer.